The role of the Sufism perspective of Imam Al-Ghazali in shaping character education at student cadres Ahlith Thoriqoh Al-Mu'tabaroh An-Nahdliyyah Nahdlatul Ulama University Cirebon - Ahmad Faisal Amin; A. Alvian Fitriyanto; Sulaeman Sulaeman (Departement of PAI, Universitas Majalengka, 2023)
The presence of phenomena that are labeled as moral degradation that currently occurs among young people is certainly a serious task in this modern era. This study aims to provide an understanding related to Sufism and its role in eroding indicators of moral decline in student cadres Ahlith Thoriqoh Al-Mu'tabaroh An-Nahdliyyah Nahdlatul Ulama University Cirebon. The results show the real impact felt by the cadres. The role of the Sufism perspective of Imam Al-Ghazali is to form character education in cadres through the development of spirituality, moral development, self-control, and the development of Emotional Intelligence. From the values above, the real impact is felt by the cadres of Ahlith Thoriqoh Al-Mu'tabaroh An-Nahdliyyah students of the Nahdlatul Ulama University of Cirebon in improving the character of individuals. This is because the activities carried out are always aligned with the values of Sufism and asasul khomsah of Ahlith Thoriqoh Al-Mu'tabaroh An-Nahdliyyah students, namely tafaqquh fi al-din, iltizamut thoat, Tasfiah al-qalb wa tazkiyat al-nafsi, Hifdz al-aurad wa al-adzkar, and khidmah lil ummah.